Application of Modified Atmosphere Preservation Technology in Cherry Storage: A Review - Lu Liu; Haiyan Lin; Xixin Zhou; Zhixu Zhang; Yi Zhang; Sengwen Deng; Shiqian Peng; Shuaikun Gong; Shiyin Guo; Wei Fan (Agriculture)
Cherries, as high-value horticultural products, have long faced preservation challenges due to their perishable nature and limited postharvest longevity. During storage and transportation, these stone fruits are particularly susceptible to quality deterioration and pathological decay, significantly impacting commercial viability and consumer acceptance. Modified atmosphere preservation (MAP) technology has emerged as the predominant preservation method for cherry storage, recognized for its operational safety, environmental controllability, and technical reliability. This review systematically examines the physiological degradation mechanisms of cherries during storage, identifies critical environmental factors influencing decay patterns, and synthesizes recent advancements in MAP applications. The analysis encompasses technological principles and efficacy evaluations of atmospheric modification, with particular emphasis on how regulated temperature, humidity, and gas composition parameters affect the bioactive compound retention, organoleptic properties, and overall eating quality—crucial factors for enhancing consumer satisfaction and market value. Furthermore, this paper critically addresses current technological limitations, including implementation costs, operational complexity, and environmental sustainability concerns. Finally, it proposes innovative optimization strategies and outlines future development trajectories to advance technological refinement and promote sustainable innovation in terms of cherry preservation methodologies.